Analysis of Inflammatory Mediators in Type 2 Diabetes Patients - Ahmed Al-Shukaili; Saif AL-Ghafri; Safia Al-Marhoobi; Said Al-Abri; Jawad Al-Lawati; Masoud Al-Maskari (International Journal of Endocrinology)
The main aim of this study is to assess the inflammatory markers in type 2 diabetes mellitus (T2DM) by measuring some cytokines concentrations and lymphocytes subset and correlate them with other laboratory investigations. Fifty-seven patients with type-2 diabetes and 30 healthy volunteers were enrolled in this study. Data for the C-reactive protein (CRP), haemoglobin, HbA1c, and autoantibody levels were obtained from the patients files. The cytokine concentrations were measured in patient’s serum using commercially available ELISA assays. Lymphocytes subsets were measured by flow cytometric methods. The levels of IL-1β, IL-6, IL-15, and TNF-α were found to be decreased in T2DM patients, whereas the levels of IL-10, IFN-γ, and caspase-1 were increased, compared to normal controls. T2DM patients with hypertension show significantly decreased levels of IL-1β and caspase-1 compared to patients without hypertension. No significant differences in lymphocytes subset between cases and normal control were observed. Significant correlations were found between HbA1c and IL-6; body mass index (BMI) was significantly correlated with CRP, TNF-α, and phosphate; the weight (Wt) was associated with CRP and IFN-γ. In conclusion, an alteration in the function of the immune system was observed in T2DM patient.